Mythe et réalités du quartier-village des travailleurs créatifs à Berriat (Grenoble) - Basile Michel (Territoire en Mouvement)
This article aims to explore the symbolic and practical relations creative workers (artists, graphic designers, etc.) have with their professional neighborhood. In order to achieve this, an analysis of the reference to the village invoked by the creative workers of the Berriat district in Grenoble is conducted. This reference is part of the discourses of inhabitants and workers who value the familiarity and conviviality that characterize their urban neighborhood. The identification of these discourses in different research works led to the definition of the concept of urban village, which accounts for the metaphorical application of the village to urban neighborhoods. The analysis conducted on the case of creative workers in the Berriat district aims to identify the constituent dimensions of the village that these workers mobilize in their discourses. This analysis is based on qualitative investigations composed of interviews, mental maps, social network analysis, documentary research and observation. These investigations show that the creative workers of Berriat give shape to the village figure through their practices and representations while articulating it with larger spatial scales. These workers anchor part of their daily practices in the quarter. They consider Berriat as an urban village separated from the rest of the city. They also develop professional and personal networks in this quarter in such a way that Berriat is animated by an internal economic and social dynamic. They mobilize the urban village of Berriat as a local resource while developing their practices and their networks beyond this spatial scale. Finally, the reference to the village invoked by creative workers is indicative of the value of the Berriat district for them as a place of social interaction and professional collaboration.